Constellations - Gardner, Jane P. (Minneapolis, MN : Pogo, 2021)
Early fluent readers will explore the science behind stars and their patterns, as well as the history behind their mapping.
Patterns in the sky -- The science of stars -- Discover the patterns.
Includes index.
2.2
K-3
520L
Keywords: Constellations -- Juvenile literature; Stars -- Juvenile literature; Constellations; Stars; Readers (Elementary) -- Nonfiction